3D imaging of cement‐based materials at submicron resolution by combining laser scanning confocal microscopy with serial sectioning. (4th February 2015) - YIO, M.H.N.; MAC, M.J.; WONG, H.S.; BUENFELD, N.R.
Summary In this paper, we present a new method to reconstruct large volumes of nontransparent porous materials at submicron resolution. The proposed method combines fluorescence laser scanning confocal microscopy with serial sectioning to produce a series of overlapping confocal z‐stacks, which are then aligned and stitched based on phase correlation. The method can be extended in the XY plane to further increase the overall image volume. Resolution of the reconstructed image volume does not degrade with increase in sample size. We have used the method to image cementitious materials, hardened cement paste and concrete and the results obtained show that the method is reliable. Possible applications of the method such as three‐dimensional characterization of the pores and microcracks in hardened concrete, three‐dimensional particle shape characterization of cementitious materials and three‐dimensional characterization of other porous materials such as rocks and bioceramics are discussed.